2014
DOI: 10.1016/j.jtcvs.2013.06.057
|View full text |Cite
|
Sign up to set email alerts
|

European experience of the convergent atrial fibrillation procedure: Multicenter outcomes in consecutive patients

Abstract: This multicenter European collaborative effort demonstrated that the convergent procedure is a safe and efficacious treatment option for persistent and long-standing persistent AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 18 publications
3
37
0
2
Order By: Relevance
“…Freedom from arrhythmia at 6 and 12 months post-procedure was 78.3% and 84.1%, respectively. Geršak et al reported similar success with convergent procedure for treatment in 76 patients with paroxysmal and non-paroxysmal AF and at 4 years follow up, 81% of patients were in sinus rhythm (86,87). Potential benefits of convergent procedure include less radiation exposure, shorter electrophysiology catheterbased procedure, reduction in the likelihood of esophageal injury that may be caused by endocardial ablation.…”
Section: Hybrid Approachmentioning
confidence: 90%
“…Freedom from arrhythmia at 6 and 12 months post-procedure was 78.3% and 84.1%, respectively. Geršak et al reported similar success with convergent procedure for treatment in 76 patients with paroxysmal and non-paroxysmal AF and at 4 years follow up, 81% of patients were in sinus rhythm (86,87). Potential benefits of convergent procedure include less radiation exposure, shorter electrophysiology catheterbased procedure, reduction in the likelihood of esophageal injury that may be caused by endocardial ablation.…”
Section: Hybrid Approachmentioning
confidence: 90%
“…More recently, the convergent procedure 92 , which combines endoscopic surgical access to the epicardial space via the diaphragm for ablation of the posterior left atrium with catheterbased endocardial ablation, has shown promise ( figure 3E). The thoracoscopic approach avoids direct trauma to the chest compared to traditional surgical approaches, while direct visualization can reduce complications while allowing large atrial areas to be targeted while confirming success via traditional electrophysiologic endpoints.…”
Section: Evolving Technical Aspects Of Ablation: Less Is Morementioning
confidence: 99%
“…More recently, the convergent procedure 92 , which combines endoscopic surgical access to the epicardial space via the diaphragm for ablation of the posterior left atrium with catheter-based endocardial ablation, has shown promise (figure 3E). The thoracoscopic approach avoids direct trauma to the chest compared to traditional surgical approaches, while direct visualization can reduce complications while allowing large atrial areas to be targeted while confirming success via traditional electrophysiologic endpoints.…”
Section: Evolving Technical Aspects Of Ablation: Less Is Morementioning
confidence: 99%
“…The thoracoscopic approach avoids direct trauma to the chest compared to traditional surgical approaches, while direct visualization can reduce complications while allowing large atrial areas to be targeted while confirming success via traditional electrophysiologic endpoints. Recent single-procedure success of 52% (and multiprocedure on-drug results of 80%) 92 are promising, and longer term assessments of success, safety and atrial function are anticipated.…”
Section: Evolving Technical Aspects Of Ablation: Less Is Morementioning
confidence: 99%